ANALISIS PENGARUH DANA ALOKASI UMUM (DAU), PAJAK DAERAH, DAN JUMLAH PENDUDUK TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI NUSA TENGGARA BARAT TAHUN 2011-2017 - Filza Andrian Maulana; Dwi Susilowati (Program Studi Ekonomi Pembangunan, 2020)
This study aims to determine the effect of general allocation funds (DAU), local taxes, and population on economic growth in West Nusa Tenggara Province. Fiscal decentralization is one form of authority that local governments have since the enactment of Law no. 22 of 1999. The implementation of fiscal decentralization was only implemented in Indonesia on January 1, 2001 based on Law no. 25 of 1999 concerning the financial balance between the central government and local governments. The variables studied are general allocation funds, regional taxes, and total population, the type of data used is secondary data with the 2011-2017 period. By using panel data analysis method. The results of the analysis show that the influence between the General Allocation Fund and Total Population variables on Economic Growth is positive and significant, while the regional tax on economic growth is significant negative